Evaluation of success of MTA pulpotomy in mature permanent carious molars with irreversible pulpitis - Farah Mushtaq; Brig. Manzoor Ahmed (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE:Pulpotomy is a common treatment for vital teeth, and recent advances in materials and techniques have extended its use to mature permanent molars with irreversible pulpitis. Vital pulp therapy encompasses various modalities, including direct and indirect pulp capping, partial pulpotomy, and full pulpotomy. In irreversible pulpitis, where pulpal inflammation is extensive, full pulpotomy is preferred to preserve the apical pulp stump. Mineral Trioxide Aggregate (MTA) has gained attention for pulpotomy due to its biocompatibility, sealing properties, and regenerative potential. This study aimed to determine the success rate of MTA pulpotomy in permanent molars diagnosed with irreversible pulpitis.METHODOLOGY:A quasi-experimental study was conducted with 103 participants aged 15 years or older. Mature permanent teeth with restorable deep carious lesions, closed apices, and cold test–based diagnosis of irreversible pulpitis were included. Exclusion criteria were tenderness on percussion/palpation, sinus tract/fistula, or pathological mobility. Treatment was performed in two visits, involving anesthesia, isolation, caries removal, and MTA placement. Outcomes were analyzed using chi-square tests to compare success rates across gender, age groups, and jaw types.RESULTS:The mean age was 24.38±6.44 years, with 42 (40.8%) females and 61 (59.2%) males. Pulpotomy success was achieved in 89.3% of cases. Comparative analysis revealed no significant differences in success by gender (p > 0.99), jaw (p > 0.99), or age group (p = 0.44).CONCLUSION:MTA pulpotomy demonstrates a high success rate and may serve as a reliable alternative to conventional root canal treatment for managing irreversible pulpitis in permanent molars.